Pengaruh Harga, Promosi, E-WOM dan Kepercayaan Terhadap Minat Pembelian Tiket Pada Patent Tour & Travel Semarang. - sopi, sopi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This study aims to analyze the effect of price, promotion, electronic word-of-mouth (e-WOM), and trust on ticket purchase interest at Patent Tour & Travel Semarang. The method used is a survey by collecting data through questionnaires distributed to 219 respondents who are Patent Tour & Travel customers. The data were analyzed using multiple regression analysis to identify the effect of each variable on purchase interest. The results of the study indicate that price and promotion have a positive and significant effect on ticket purchase interest. In addition, e-WOM has also been shown to contribute significantly to increasing purchase interest, while trust shows the strongest influence among other variables. This study provides recommendations for Patent Tour & Travel management to utilize promotional strategies more and strengthen consumer trust elements to increase ticket purchase interest. These findings are expected to be a reference for companies in formulating more effective marketing strategies. Keywords: price, promotion, e-WOM, trust, purchase interest, Patent Tour & Travel.